GROWTH PERFORMANCE OF NELLORE SYNTHETIC BREED OF SHEEP (Indian Journal of Animal Production and Management, 2016)
A synthetic breed named as “Nellore Synthetic” was evolved at Livestock Research Station, Palamaner,  Andhra Pradesh was developed by crossing of the Nellore sheep of Andhra Pradesh with the exotic breeds  of Dorset and Suffolk by stabilizing the exotic inheritance at 50%. Data on various body weights were  subjected to least square analysis of variance by using fixed effect model to estimate the effect of various  non genetic factors Data on various body weights were subjected to least square analysis of variance by  using fixed effect model to estimate the effect of various non genetic factors. Overall mean birth weight of  Nellore sheep at birth, weaning, 6, 9 and 12 months of age were 3.40±0.02 kg, 13.35±0.07kg, 17.78±0.09  kg, 20.03±0.11 kg and 22.47±0.12 kg respectively. All body weights were significantly (P
Keywords: Birth weight; Body weights; Nellore synthetic sheep; Season; Sex